Buying and Selling Imitation Products in the Perspective of Fiqh Muamalah - Dahmayanti, Andi; Hawariah, Hawariah; Risdayani, Risdayani; Musriwan, Musriwan; Atikah, Nurul (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyse the fiqh muamalah review of the practice of buying and selling imitation products, which is now rampant in contemporary economic transactions. The type of research used is library research with a normative approach and deductive analysis. The results of the study show that formally, the sale and purchase of imitation products has fulfilled the pillars and requirements of the contract, namely the existence of ijab-kabul and the element of willingness (riḍā) between the seller and the buyer. However, from a broader perspective of fiqh muamalah, this practice is categorised as a transaction that is haram and prohibited. This prohibition is based on the existence of an element of ḍarar (harm) to a third party, namely the original manufacturer whose intellectual property rights are violated without permission or tolerance. In addition, this practice contains elements of tadlīs (deception) and garar related to the uncertainty of the quality of products that resemble the original goods but do not have the same quality standards. This study concludes that even though the formal requirements are met, the violation of other people’s property rights and the element of manipulation make this transaction incompatible with the principles of Islamic justice. The results of this study are expected to serve as a reference for academics, the government, and the public in understanding the limits of transaction honesty and the protection of the rights of original producers in order to create a muamalah ecosystem that is free from injustice.